Insurance law in China - Hjalmarsson, Johanna; Huang, Dingjing (Contemporary commercial law, 2015)
"The Chinese insurance market is expanding enormously as risk adversity takes hold in the economy while the role of the State as guarantor of commerce is gradually reduced. In addition, insurance is a heavily regulated field with detailed contract law stipulations. An introduction to regulation and contract law and an understanding of current issues is essential for someone seeking to do business in the Chinese market. Insurance law is also a field that translates well from one jurisdiction to another, and academics will be interested in understanding how issues are dealt with in another jurisdiction.The book seeks to present and discuss current topics in Chinese insurance law and regulation to an English-speaking audience knowledgeable of common law insurance law and international insurance business. The combined effect of the papers is to present Chinese insurance law to an audience unfamiliar with Chinese law, in a readable and accessible essay chapter format. Each chapter is written by an expert in the field and goes beyond a basic introduction to provide in depth well-researched information and academic analysis on the topic in question"--